Advancing towards the implementation of ecosystem-based environmental impact assessment for coastal zone. (1st December 2021) - Andrade, M.M.; Turra, A.
Abstract: Impacts caused by human developments threaten environmental quality and health of coastal social-ecological systems. Integrated frameworks based on ecosystem processes and services (ES), such as Ecosystem-Based Management (EBM), are being proposed to estimate such changes and improve tools, as Environmental Impact Assessment (EIA). We used some elements of a contested port expansion in Brazil (i.e., stakeholders with varying degrees of relationship with the study area; future disturbance scenarios associated with the port expansion; and different ES that might be affected) to evidence how EBM can qualify coastal EIA. We performed in-depth interviews with four different groups of stakeholders and analyzed their speeches and argumentation patterns to assess the ES in current and potential disturbance scenarios. The groups had different perceptions from each other, which depended on the scenario and ES evaluated. Groups more engaged with the place returned more comprehensive assessments of changes in the ES analyzed, with a clearer understanding of cause-effect relationships. Stakeholders' perceptions reflected trade-offs of the local urban conflicts. This experimental EBM approach provided a higher variety and a more integrated assessment of impacts than the EIA of the port expansion. This study provides evidence that the EBM approach has the potential to qualify the EIA through engaging local stakeholders and capturing the Traditional Ecological Knowledge about the structure and functioning of the ecosystem as well as allowing a more straightforward rationale to link the development activities with their consequences to society. Graphical abstract: Image 1 Highlights: People, ecosystem services, uses and impacts are all connected in coastal systems. Changes in coastal systems require Ecosystem-Based Impact Assessments. Impact Assessments based on ecosystem services support appropriate decision-making. Social participation strengthen communities and attributes of coastal systems.